2009
DOI: 10.1177/070674370905400206
|View full text |Cite
|
Sign up to set email alerts
|

An Examination of DSM-IV Borderline Personality Disorder Symptoms and Risk for Death by Suicide: A Psychological Autopsy Study

Abstract: Objective: To clarify whether certain Diagnostic and Statistical Manual of Mental Disorders, Fourth Edition (DSM-IV), borderline personality disorder (BPD) symptoms are more prevalent among people who die by suicide, and thereby better predict suicide risk. Method:A psychological autopsy method with best informants was used to investigate DSM-IV BPD symptoms and suicide risk among people who died by suicide and met criteria for BPD (n = 62), and BPD control subjects (n = 35).Results: BPD symptoms in people who… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
22
0
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 26 publications
(26 citation statements)
references
References 39 publications
3
22
0
1
Order By: Relevance
“…70 In a recent study about borderline personality symptoms and risk for death by suicide, McGirr et al showed that patients who completed suicide, borderline personality disorder symptoms were less likely to include affective instability and paranoid ideationdissociative symptoms, suggesting that these symptoms could be associated with suicide attempts but not with death by suicide. 74 These findings support the proposition that suicide attempts and death by suicide in patients with borderline personality and other disorders are phenomenologically distinct. 7) Impulsiveness, hostility, aggressiveness and hopelessness Impulsiveness, hostility and aggressiveness are risk factors for suicidal behavior in different psychiatric samples.…”
Section: ) Rapid Cyclingsupporting
confidence: 72%
“…70 In a recent study about borderline personality symptoms and risk for death by suicide, McGirr et al showed that patients who completed suicide, borderline personality disorder symptoms were less likely to include affective instability and paranoid ideationdissociative symptoms, suggesting that these symptoms could be associated with suicide attempts but not with death by suicide. 74 These findings support the proposition that suicide attempts and death by suicide in patients with borderline personality and other disorders are phenomenologically distinct. 7) Impulsiveness, hostility, aggressiveness and hopelessness Impulsiveness, hostility and aggressiveness are risk factors for suicidal behavior in different psychiatric samples.…”
Section: ) Rapid Cyclingsupporting
confidence: 72%
“…Previous studies conducted by our investigator group (20,25,(45)(46)(47), as well as other researchers (30)(31)(32), on the validity of the proxy-based behavioral assessments used in the present study demonstrate the similarity between information obtained from an informant and information obtained from the subject.…”
Section: Assessmentssupporting
confidence: 72%
“…Ce trouble, caractérisé par une impulsivité et une instabilité de l'humeur, des relations interpersonnelles et de l'image de soi, est le seul trouble mental qui inclut les comportements autoagressifs récurrents dans ses critères diagnostiques (American Psychological Association [APA], 2013). La prévalence à vie de décès par suicide chez les personnes de la population générale qui ont un trouble de la personnalité limite se situe entre 5 et 10 % (Berk, Jeglic, Brown, Henriques et Beck, 2007 ;McGirr, Paris, Lesage, Renaud et Turecki, 2009). Ce trouble de personnalité est surreprésenté dans les milieux carcéraux, la prévalence variant de 25 à 50 %, selon la métho-dologie utilisée, avec une plus forte représentativité chez les détenues (Sansone et Sansone, 2009).…”
Section: Mots Clés • Prison Tentative De Suicide Tdah Santé Mentaleunclassified